Observational constraint on momentum flux-gradient relationships reduces modeling biases of PBL mixing of particles in urban area - Qike Yang; Chun Zhao; Renmin Yuan; Zining Yang; Qiuyan Du; Mingyue Xu; Yubin Li; Kaihui Xia (Environmental Research Communications)
The momentum flux-gradient relationships within the urban roughness sublayer deviate from the classical relationships proposed by the Monin-Obukhov similarity theory. Despite this discrepancy, prevailing atmospheric models persistently rely on these classical relationships, which were originally derived from natural, homogeneous surfaces. This practice may introduce significant errors when simulating urban atmospheric pollution. This study utilized meteorological parameters and turbulent fluxes obtained from field measurements in the urban roughness sublayer to re-establish momentum flux-gradient relationships. Compared to non-urban areas, the flux-gradient relationships in the urban environments exhibit significant deviations under stable conditions. Consequently, we revised a planetary boundary layer parameterization to incorporate new urban flux-gradient relationships. The revised scheme was implemented in the WRF-Chem model, and the simulation results demonstrated a marked reduction in modeling biases under stable conditions, particularly for relatively developed cities in Eastern China.